Five Little Monkeys sitting in a tree - Christelow, Eileen (New York : Scholastic, 1991)
While mama takes a nap, five little monkeys tease mr. crocodile. "can't catch me" they shout, and Mr. Crocodile opens his big mouth: SNAP! Oh no, now there are only four monkeys- or so it seems.
Keywords: Counting